Pengaruh Supervisi Akademik Terhadap Disiplin Kerja Guru pada Masa Pandemi Covid-19 - Ruiyah Ruiyah; Husain AS; Elpisah Elpisah (IAI Darussalam, 2022)
Abstract The purpose of this research was to: (1) the description of academic supervision during the COVID-19 pandemic period, (2) the description of teacher work discipline during the COVID-19 pandemic period, and (3) the significant effects of academic supervision on teacher work discipline during the covid-19 pandemic period. The type of research is descriptive quantitative. The populations in the study were all 23 teachers. The sampling technique was a saturated sampling, so that the samples of 23 people were selected. Data collection techniques used were questionnaires and documentation. The data analysis technique was carried out using a descriptive analysis in the form of percentages and inferential analysis using analyses of prerequisite tests, hypothesis testing and coefficient determination tests. The results showed that (1) the description of academic supervision during the covid-19 pandemic period descriptively tended to be in very good criteria, with a percentage of 93.48%, (2) the description of teacher work discipline during the covid-19 pandemic period descriptively tended to be in very good criteria, with a percentage of 89.49%, and (3) there was a significant influence of academic supervision on teacher work discipline during the covid-19 pandemic period, where the probability value was fewer than the significant level (0.034 < 0.05).